2007
DOI: 10.1001/archneur.64.3.noc60123
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid tau/β-Amyloid42 Ratio as a Prediction of Cognitive Decline in Nondemented Older Adults

Abstract: To investigate the ability of cerebrospinal fluid (CSF) and plasma measures to discriminate early-stage Alzheimer disease (AD) (defined by clinical criteria and presence/absence of brain amyloid) from nondemented aging and to assess whether these biomarkers can predict future dementia in cognitively normal individuals. Design: Evaluation of CSF ␤-amyloid 40 (A␤ 40), A␤ 42 , tau, phosphorylated tau 181 , and plasma A␤ 40 and A␤ 42 and longitudinal clinical follow-up (from 1 to 8 years). Setting: Longitudinal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

66
714
4
8

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 848 publications
(792 citation statements)
references
References 25 publications
66
714
4
8
Order By: Relevance
“…In studies of nondemented older adults, higher CSF tau:A␤ 42 ratios were associated with higher rates of subsequent progression to the clinical stages of AD (34). The findings from these and other studies suggest that brain imaging and CSF measurements have complementary roles in the presymptomatic detection and tracking of AD.…”
Section: Discussionmentioning
confidence: 60%
“…In studies of nondemented older adults, higher CSF tau:A␤ 42 ratios were associated with higher rates of subsequent progression to the clinical stages of AD (34). The findings from these and other studies suggest that brain imaging and CSF measurements have complementary roles in the presymptomatic detection and tracking of AD.…”
Section: Discussionmentioning
confidence: 60%
“…Many studies demonstrated that the levels of CSF Aβ42 in AD are decreased compared with controls [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] . CSF Aβ42 can differentiate AD from controls with 89% sensitivity and 90% specificity [51] .…”
Section: Csf Aβ42 As a Biomarker Of Admentioning
confidence: 99%
“…All CDR 1 individuals had received a diagnosis of DAT. For each individual LP, fasted CSF (20-30 mL) was collected, gently mixed, centrifuged, aliquoted (0.5 mL) and frozen at 280uC in polypropylene tubes (2.0 mL tubes for storage) as described [3]. For preparation of pooled sample aliquots, all selected 0.5 mL samples were simultaneously thawed in an ice slurry within a 4uC room, combined and gently but thoroughly mixed in larger polypropylene tubes, re-aliquoted (0.5 mL) into fresh pre-chilled 2.0 mL polypropylene tubes, and frozen and stored at 280uC until use.…”
Section: Participant Selection and Sample Preparationmentioning
confidence: 99%
“…Pittsburgh compound B, or PIB) and positron emission tomography, or indirectly, by measuring low CSF beta-amyloid42 (Ab42) concentrations that correlate with amyloid deposition [3,[10][11][12][13][14]. Imaging and fluid biomarker studies have also shown potential to predict cognitive decline by measuring amyloid deposition [5], regional volumetric and metabolic changes in the brain [15][16][17], or specific changes in the CSF proteome (including concentrations of tau, YKL-40, VILIP-1, and calbindin, each in association with Ab42) [2,3,18,19]. CSF analysis may even allow classification of disease stage [20] and monitoring of acute changes in response to disease modifying therapies, as illustrated recently with gamma-secretase inhibitors [21].…”
Section: Introductionmentioning
confidence: 99%